Evaluation of Sudanese nurse’s competence in automated external defibrillator (AED) knowledge and performance: Aquasi-experimental hospital base study in Khartoum locality - Elturabi Elsayed Ebrahim (International Journal of Africa Nursing Sciences, 2024)
Background: The Automated External Defibrillator represents a cornerstone of life-saving interventions, essential for responding to cardiac emergencies both within hospital walls and in community settings. Nurses shoulder the responsibility of understanding the correct protocols for AED usage, as their proficiency can be pivotal in administering timely and effective interventions during instances of cardiac arrest, significantly increasing the chances of survival. Purpose: The aim of this study Assess of Sudanese nurses Competency in Automated External Defibrillator (AED) knowledge and performance: in Khartoum Sudan. Methods: A quasi-experimental study conducted in 2023 aimed to evaluate the competencies of 100 qualified nurses regarding their knowledge and performance related to Automated External Defibrillators (AEDs). Throughout the study, seminars and lectures were delivered to the nursing staff to enhance their understanding of AED usage. Nurse performance was measured by conducting an applied experiment involving a mannequin and an AED, and following the prescribed steps. Data collection was carried out using questionnaires and observation checklists, with subsequent analysis conducted using the statistical software SPSS. Result: The study findings indicate a predominant representation of female participants, comprising 65 % of the total sample, with a significant portion falling within the 18 to 30 years age bracket. Among the participants, the majority, at 56 %, held a B.Sc. degree, followed by diplomas (25 %), master's degrees (5 %), and Ph.D. qualifications (2 %). Surprisingly, 57 % of participants had not undergone prior training in AED usage. The study's pre-test mean for knowledge stood at 16 %, increasing substantially to 84 % in the post-test phase, with a statistically significant P-value of 0.000, reflecting a marked improvement in knowledge. Similarly, the pre-test mean for performance was 19.1 %, rising to 80.1 % in the post-test phase, with a corresponding P-value of 0.000, indicating a significant enhancement in performance. These findings collectively suggest a positive shift towards improved knowledge and performance in AED usage among the participants. Conclusion: Study concludes improves nurses’ knowledge and performance in Automated External Defibrillator.